An accidental statistician : the life and memories of George E.P. Box - Box, George E. P. (John Wiley and Sons, Inc., 2013)
Celebrating the life of an admired pioneer in statisticsIn this captivating and inspiring memoir, world-renowned statistician George E.P. Box offers a firsthand account of his life and statistical work. Writing in an engaging, charming style, Dr. Box reveals the unlikely events that led him to a career in statistics, beginning with his job as a chemist conducting experiments for the British army during World War II. At this turning point in his life and career, Dr. Box taught himself the statistical methods necessary to analyze his own findings when there were no statist.